Model Optimasi Produksi Kue Menggunakan Metode Simpleks Pada Toko Kue Rosalina Cabang Jatake - Lestari, Sri; Sholehah, Sholehah; Muttaqien, Zaenal (Journal Industrial Manufacturing, 2023)
The continuity and development of the cake production business needs to be maintained with steps to be able to allocate raw materials and increase profits. Therefore, an effort is needed using a method in determining the right combination of production factors from the products made and the combination of products produced. This problem can be overcome by creating an optimization model using the simplex method. The simplex method is a method that mathematically starts from a basic feasible solution to another basic feasible solution and is done repeatedly (iterative) so that finally an optimal basic solution is obtained. The optimum value is obtained by analyzing whether the resources have been fully used (scarce) or excessively (Abundant) used with the optimal simplex table approach. Based on the results of iteration 3, it is obtained that line Z no longer has a negative value so that the solution obtained is optimal, meaning that Rosalina Bakery cake shop if you want to get maximum profit, it produces brownie cakes (x1) as much as 3.3333; Bolu Pandan (x2) as much as 8.6667. The maximum profit will be achieved at Rp 93,999.9 rounded up to Rp 94.000,- per day. Based on the results of the analysis, it shows that the cake production optimization model can help maximize profits from limited resources..Keywords: model, simplex, optimization, production, profit, maximum